Increased risk of prediabetes among virally suppressed adults with HIV in Central Kenya detected using glycated haemoglobin and fasting blood glucose. Issue 4 (17th July 2021) - Njoroge, Anne; Augusto, Orvalho; Page, Stephanie T.; Kigondu, Christine; Oluka, Margaret; Puttkammer, Nancy; Farquhar, Carey
Abstract: Aims: As survival among people living with HIV (PLHIV) improves with universal HIV treatment, new strategies are needed to support management of co‐morbidities like type 2 diabetes (T2D). We assessed prediabetes and T2D prevalence and risk factors using haemoglobin A1c (HbA1c) among PLHIV on antiretroviral therapy (ART) in Central Kenya. Methods: This cross‐sectional study, conducted at a rural and urban site, enrolled PLHIV aged ≥35 years on ART for at least 5 years. HbA1c was assayed using Cobas b 101 ®, a point‐of‐care device. HbA1c levels ≥6.5% were considered diagnostic of T2D. For pre‐diabetic HbA1c levels (5.7%–6.4%), participants were requested to return the following day for a fasting blood glucose (FBG) to rule out T2D. Risk factors were assessed using multivariable log‐binomial regression. Results: Of the 600 completing study procedures, the prevalence of diabetes was 5% (30/600). Ten participants were known to have diabetes; thus, prevalence of newly diagnosed T2D was 3.4% (20/590). Prevalence of prediabetes (HbA1c 5.7%–6.4%) was 14.2% (84/590). Significant predictors of elevated HbA1c were increase in age (Prevalence ratio [PR]: 1.10, CI: 1.02, 1.18, p = .012), hypertension (PR: 1.43, CI: 1.07–2.3, p = .015), central adiposity (PR: 2.11, CI: 1.57–2.84, p < .001) and use of Efavirenz (PR: 2.09, CI: 1.48, 2.96, p < .001). Conclusion: There is a high prevalence of prediabetes, a significant predictor of T2D, among PLHIV in Central Kenya. Point‐of‐care HbA1c may help identify PLHIV with prediabetes in a single screening visit and provide an opportunity for early intervention. Abstract : The article highlights the need for T2D screening especially among African people with HIV who are aviremic using standard diagnostic measures. The results show a high prevalence of prediabetes (14%) with a significant proportion of them expected to develop overt diabetes and ultimately its costly complications.